Levodopa induced ON-OFF motor fluctuations in Parkinson's disease related to rhythmical masticatory jaw movements. Issue 4 (April 1992) - Karlsson, S; Persson, M; Johnels, B
Abstract : The motor disturbance in Parkinson's disease affects all voluntary movement, including innate rhythmical processes such as gait, breathing, and chewing. While there are good descriptions and pathophysiological hypotheses of the changes in gait less is known about the way masticatory movements are affected. By means of a three-dimensional optoelectronic recording technique the differences were investigated in mandibular movement displacement, velocity, and masticatory cycle duration during levodopa induced OFF and ON states. Recordings were made before ordinary morning medication and one hour after medication with 200 mg levodopa and a decarboxylase inhibitor (madopar). There were no differences before and after medication in the opening and closing duration of the masticatory cycle, but a significantly decreased occlusal level phase duration in the ON state was seen. Mandibular velocity and mandibular movement amplitude were significantly greater after medication. Thus the changes in dopamine transmission selectively influenced parts of the masticatory cycle but not the fundamental rhythmical pattern.